Effects of the Medicaid Continuous Enrollment Requirement on Access to Reconstructive Breast Surgery - Liang, Joey; Lin, Elaine; Shammas, Ronnie L.; Patel, Ash; Phillips, Brett T. (Journal of Reconstructive Microsurgery, 2025)
The “continuous enrollment provision” of the Families First Coronavirus Response Act of 2020 (FFCRA) maintained states' Medicaid enrollments throughout the COVID-19 public health emergency. This study evaluated the impact of the continuous enrollment requirement on Medicaid patients' access to reconstructive breast surgery.A retrospective cohort study was conducted on all patients who received reconstructive breast surgery procedures at a large academic institution between July 1, 2013, and July 1, 2023. The Medicaid continuous enrollment period was defined as March 18, 2020, to July 1, 2023. Univariate analysis, multivariable logistic regression, and difference-in-difference analysis were performed.Three thousand five hundred sixty-four patients were included, of whom 252 patients were insured by Medicaid. Patients' odds of Medicaid insurance before and during the continuous enrollment period did not differ (p = 0.096). The distribution of Medicaid and non-Medicaid insurance among autologous breast reconstruction patients similarly did not differ during the continuous enrollment period (p = 0.86). Difference-in-difference analysis confirmed that Medicaid prevalence among autologous breast reconstruction patients did not change with the continuous enrollment requirement (p = 0.07). Increased age was predictive of Medicaid insurance (odds ratio [OR]: 1.043; p < 0.001); however, age-dependent differences decreased during the continuous enrollment period. Patients with non-English language preferences had lower odds of Medicaid insurance (OR: 0.38; p = 0.035); this difference remained unchanged with the continuous enrollment requirement (p = 0.59).The continuous enrollment requirement alleviated certain age-dependent barriers for Medicaid patients but may not have addressed other patient-level, system-level, and procedure-specific barriers to reconstructive breast surgery.
Keywords: Medicaid; health policy; breast